E pluribus unum : nineteenth-century American literature & the Constitutional paradox - Harris, W. C. (William Conley) (University of Iowa Press, 2005)
"Out of many, one." But how do the many become one without sacrificing difference or autonomy? This problem was critical to both identity formation and state formation in late 18th- and 19th-century America. The premise of this book is that American writers of the time came to view the resolution of this central philosophical problem as no longer the exclusive province of legislative or judicial documents but capable of being addressed by literary texts as well. The project of E Pluribus Unum is twofold. Its first and underlying concern is the general philosophic problem of the one and the man